2017
DOI: 10.1002/14651858.cd011289.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular electrical stimulation (NMES) for patellofemoral pain syndrome

Abstract: This review found insufficient and inconclusive evidence from randomised controlled trials to inform on the role of NMES for treating people with PFP in current clinical practice. The very low-quality evidence available means that we are uncertain whether or not a multiple-session programme of NMES combined with exercise over several weeks versus exercise alone results in clinically important differences in knee pain and function at the end of the treatment period or at one year. There were no data on adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 49 publications
0
17
0
1
Order By: Relevance
“…Treatment options also include physical therapy, psychotherapy, mesotherapy, whole-body cryotherapy, and alternative or complementary therapies acupuncture, prolotherapy, percutaneous electrical nerve stimulation, and neuromuscular electrical stimulation. The current treatment provides some relief of acute or short-lasting pain but is unsatisfactory for chronic musculoskeletal pain (78)(79)(80)(81). A recent report showed that transcranial magnetic stimulation of the prefrontal cortex attenuated long-term experimental muscle pain in human subjects (14).…”
Section: Treatment Opportunitiesmentioning
confidence: 99%
“…Treatment options also include physical therapy, psychotherapy, mesotherapy, whole-body cryotherapy, and alternative or complementary therapies acupuncture, prolotherapy, percutaneous electrical nerve stimulation, and neuromuscular electrical stimulation. The current treatment provides some relief of acute or short-lasting pain but is unsatisfactory for chronic musculoskeletal pain (78)(79)(80)(81). A recent report showed that transcranial magnetic stimulation of the prefrontal cortex attenuated long-term experimental muscle pain in human subjects (14).…”
Section: Treatment Opportunitiesmentioning
confidence: 99%
“…The multimodal treatment program was designed based on the usual exercises and modalities used in local clinics. 19,20,31,49 All patients received a standard, supervised, 60-minute multimodal treatment 3 times per week for 6 weeks. Table 1 shows the details of the multimodal rehabilitation program.…”
Section: Multimodal Treatmentmentioning
confidence: 99%
“…A 2017 Cochrane Review by Martimbianco et al found limited, low-quality regarding the effect of NMES for the treatment of PFP (74). The review concluded that very low-quality evidence suggests NMES reduces pain at the end of treatment (3 to 12 weeks) but the improvement may not be clinically relevant given the small magnitude of change (1.63 out of 10 on the visual analog scale).…”
Section: Treatmentmentioning
confidence: 99%
“…The review concluded that very low-quality evidence suggests NMES reduces pain at the end of treatment (3 to 12 weeks) but the improvement may not be clinically relevant given the small magnitude of change (1.63 out of 10 on the visual analog scale). The authors found even less support for NMES on strength or function, concluding that “insufficient and inconclusive evidence” exists for the effect of NMES on treating individuals with PFP (74). While one pilot study has found no statistically significant differences between 38 athletes (19 per group) who completed physiotherapy or physiotherapy plus electrical stimulation, limitations including study design, follow-up, and stimulation parameters limit its applicability (75).…”
Section: Treatmentmentioning
confidence: 99%